Animal welfare in Latin America: Trends and characteristics of scientific publications - Gallo, Carmen; Véjar, Lorena; Galindo, Francisco; Huertas, Stella M.; Tadich, Tamara (Frontiers in Veterinary Science, 2022)
The present study constitutes a review of the scientific articles about animal welfare in terrestrial farmed animals, published in 19 countries of Latin America. The main objectives were to quantify and characterize articles produced between 1992 and 2021 in farm animals’ welfare using "Web of Science [v.5.32]" and "CAB Abstracts " databases. A total of 663 articles were found for the period analyzed, which were mainly in English (87%). The countries with the most publications were Brazil (43%), México (25%), Chile (12%), Uruguay (10%), Colombia (4%) and Argentina (2%). Cattle was the farm species most considered in the publications (41%), and the studies addressed mostly the on-farm production stage (76%). There was a rapid increase in the number of articles published in the last 15 years, accounting for 95% of the publications. This could be related to the publication of welfare standards by the World Organization for Animal Health (WOAH) since 2005, the creation of the Collaborating Centre for Animal Welfare and Sustainable Livestock Systems—Chile-Uruguay-México in 2009, a Regional Strategy of Animal Welfare prompted by the WOAH in 2012 and the inclusion of animal welfare in the veterinary curriculum. The fact that most articles were in English shows that Latin American researchers have somehow overcome the challenge of publishing in a non-native language and their research can be read/cited worldwide. However considerable gaps in scientific productivity were identified in comparison to European and North American countries. Scientific research concerning the livestock industry in Latin America faces new challenges arising from the need to move toward more sustainable production systems within the One Welfare and One Health frame.